PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII.7 SMP NEGERI 5 PEKANBARU - Mukhlisatul Humaira Syaifar; Susda Heleni; Atma Murni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is a class action research that aims to improve the learning process and mathematics learning outcomes through the implementation of the Problem Based Learning (PBL) model. The subjects of this research were VIII.7 grade students of SMP Negeri 5 Pekanbaru in the academic year 2019/2020, which total of participants are 38 students, consists of 20 male students and 18 female students. The research instrument consisted of mathematical learning instruments in the form of syllabus, lesson plans, student worksheet and data collection instruments in the form of observation sheets and mathematics learning outcomes tests. Data from the observation were analyzed with narrative descriptive analysis techniques and data from learning outcomes tests were analyzed with descriptive statistical analysis techniques. Based on the observation sheet analysis, the implementation of the PBL model can improve the learning process as indicated by an increase in teacher activity and student sheets activity in each cycle. This gives an influence on student learning outcomes. The percentage of students who achieved the minimum criteria of mastery learning increased from 7 students (18.42%) to 18 students (47.37%) during UH I and to 24 students (63.16%) in UH II. The results of this research indicate that the implementation of the Problem Based Learning (PBL) model can improve the learning process and mathematics learning outcomes of students in class VIII.7 SMP Negeri 5 Pekanbaru odd semester 2019/2020 academic year on the material system of linear two-variable equation.Key Words: Mathematics Learning Outcomes, Problem Based Learning, Classroom Action Research